Seafloor biodiversity of Canada's three oceans: Patterns, hotspots and potential drivers. Issue 2 (9th December 2019) - Wei, Chih‐Lin; Cusson, Mathieu; Archambault, Philippe; Belley, Renald; Brown, Tanya; Burd, Brenda J.; Edinger, Evan; Kenchington, Ellen; Gilkinson, Kent; Lawton, Peter; Link, Heike; Ramey‐Balci, Patricia A.; et al.
Abstract: Aim: We examined the relationships between bathymetry, latitude and energy and the diversity of marine benthic invertebrates across wide environmental ranges of Canada's three oceans. Location: Canadian Pacific, Arctic and Atlantic Oceans from the intertidal zone to upper bathyal depths, encompassing 13 marine ecoregions. Methods: We compiled 35 benthic datasets that encompass 3, 337 taxa (70% identified to species and 21% to genus) from 13, 172 samples spanning 6, 117 sites. Partitioning the analyses by different gear types, ecoregions or sites, we used Hill numbers to examine spatial patterns in α‐diversity. We used resampling and extrapolation to standardized sampling effort and examined the effects of depth, latitude, chemical energy (export particulate organic carbon [POC] flux), thermal energy (bottom temperature) and seasonality of primary production on the benthic biodiversity. Results: The Canadian Arctic harboured the highest benthic diversity (e.g. epifauna and common and dominant infauna species), whereas the lowest diversity was found in the Atlantic. The Puget Trough (Pacific), Beaufort Sea, Arctic Archipelago, Hudson Bay, Northern Labrador and Southern Grand Bank (Atlantic) were the "hotspots" of diversity among the ecoregions. The infauna and epifauna both exhibited hump‐shaped diversity–depth relationships, with peak diversity near shelf breaks; latitude (positively) predicted infaunal diversity, albeit weakly. Food supply, as inferred from primary production and depth, was more important than thermal energy in controlling diversity patterns. Limitations with respect to calculating POC flux in coastal (e.g. terrestrial runoff) and ice‐covered regions or biological interactions may explain the negative POC flux–infaunal diversity relationship. Main Conclusions: We show previously unreported diversity hotspots in the Canadian Arctic and in other ecoregions. Our analyses reveal potential controlling mechanisms of large‐scale benthic biodiversity patterns in Canada's three oceans, which are inconsistent with the prevailing view of seafloor energy–diversity relationships. These results provide insightful information for conservation that can help to implement further MPA networks.